Perlindungan Hukum Terhadap Anak Yang Menjadi Korban Penculikan Dalam Perspektif Undang-Undang Nomer 35 Tahun 2014 Jo Undang-Undang Nomer 23 Tahun 2002 - Fuji Raihan Azhari Kusworo; Tanti Kirana Utami; Ervina Auralia; Desta Cantika; Moch Rifat Novri Raya Mulyana; Dendi Aulia (Indonesian Journal Publisher, 2025)
Child abduction not only violates human rights but also threatens the future of children who will become the next generation of a nation. In Indonesian law, the protection of children who are victims of abduction is regulated under various laws, including Law Number 35 of 2014, which is an amendment to Law Number 23 of 2002 concerning Child Protection. A child is a legal subject with special characteristics, whose rights are protected and regulated by specific laws and regulations. Indonesia is a rule of law country as stated in Article 1, Paragraph (3) of the 1945 Constitution of the Republic of Indonesia. The Indonesian Constitution, UUD 1945, as the highest legal norm, stipulates that “Every child has the right to survival, growth, and development, and has the right to protection from violence and discrimination.”